A Miniaturized Mechatronic System Inspired by Plant Roots for Soil Exploration - Mazzolai, Barbara; Mondini, Alessio; Corradi, Paolo; Laschi, Cecilia; Mattoli, Virgilio; Sinibaldi, Edoardo; Dario, Paolo (IEEE/ASME transactions on mechatronics, 2011)
This paper describes the principles and theoretical investigations, supported by experimental measurements, aimed at designing and developing a novel mechatronic system for soil exploration, inspired by the apical part of the plant roots, named apex. Each single plant root has to move through the substrate, orienting itself along the gravity vector and locating water and nutrients. In the same way, the mechatronic apex can steer in all directions and it embeds a gravity sensor, a soil moisture gradient detector, as well as the electronics for sensory data acquisition and steering control. A bio-inspired algorithm reproducing the gravitropism and hydrotropism behaviors, typical of plants, was developed and tested on a purposive prototype of the mechatronic apex system, actuated by hydraulic pumps. Moreover, the design and testing of a novel bio-inspired osmotic actuator module, composed of three cells separated by couples of osmotic and ion-selective membranes, is also presented. Preliminary prototypes developed in acrylic material for testing the gravitropism and hydrotropism behaviors are shown.